Short-Chain Alcohols Upregulate GILZ Gene Expression and Attenuate LPS-Induced Septic Immune Response - Ng, Hang Pong; Wang, Yubo; Jennings, Scott; Nelson, Steve; Wang, Guoshun (Frontiers in Immunology, 2020)
Alcohol differentially affects human health, depending on the pattern of exposure. Moderate intake provides beneficial anxiolytic and inflammosuppressive effects, while excessive consumption leads to alcohol use disorders. The mechanism underlying this bi-phasic working mode of alcohol has not been clearly defined. Our previous publication demonstrates that ethanol, in the absence of glucocorticoids (GCs), induces expression of Glucocorticoid-Induced Leucine Zipper (GILZ), a key molecule that transduces GC anti-inflammatory and immunosuppressive effect (Ng. et al, Front Immunol. 2017). Here we report that similar short-chain alcohols, propanol and isopropanol, share the same property in upregulating GILZ gene expression and suppressing cell inflammatory response in vitro. When mice were exposed to these alcohols, respectively, GILZ gene expression was augmented in peripheral blood leukocytes in a dose-dependent manner. These short-chain alcohols suppressed host inflammatory response to LPS and significantly reduced LPS-induced mortality in mice. Intriguingly, propanol and isopropanol displayed more potent protection than ethanol at the same dose. Moreover, inhibition of ethanol metabolism enhanced the ethanol protective effect, suggesting that it is ethanol, instead of its derivatives, that confers immune suppression. Taken together, short-chain alcohols per se upregulate GILZ gene expression, and provide immune protection against LPS, suggesting a critical role of GILZ in alcohol influence of human health.